Number 1 of a series of fire prevention posters from the PLA Chongqing Public Security organs, Procuratorial organs and People's Courts Military Control Commission Fire Prevention Branch. Call numbers set: BG E37/318-323 (1967)
Number 1 of a series of fire prevention posters from the PLA Chongqing Public Security organs, Procuratorial organs and People's Courts Military Control Commission Fire Prevention Branch. Call numbers set: BG E37/318-323.